1993
DOI: 10.1021/j100122a011
|View full text |Cite
|
Sign up to set email alerts
|

Multicoincidence mass spectrometry applied to hexamethyldisilane excited around the silicon 2p edge

Abstract: Photoelectron-photoion-photoion coincidence (PEPIPICO) mass spectrometry is applied to Si 2p core ionization.The ion yield spectrum is compared to the spectrum of the tetramethylsilane molecule in order to point out resonances due to the Si-Si chemical bond. Simple coincidence mass spectra are dominated by the SiC3HgC fragment ion and do not show a strong dependence on photon wavelength. PEPIPICO spectra demonstrate that dissociation dynamics is dominated by stepwise fragmentation of SiC3H9+ and that double io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 6 publications
3
105
0
1
Order By: Relevance
“…The time-of-flight correlation plots from the triple coincidences follow the same pattern since the slope ⌬T S + / ⌬T O + Ϸ −1.2 because the time deviation is proportional to the momentum deviation. 27 We also studied Dalitz plots for the dicationic three-body breakups and found that both C / O + / S + and C + / O + / S display uncorrelated patterns similar to those in Figs. 3͑c͒ and 3͑d͒, thus confirming the concerted dissociation.…”
Section: Fragment Correlationmentioning
confidence: 69%
“…The time-of-flight correlation plots from the triple coincidences follow the same pattern since the slope ⌬T S + / ⌬T O + Ϸ −1.2 because the time deviation is proportional to the momentum deviation. 27 We also studied Dalitz plots for the dicationic three-body breakups and found that both C / O + / S + and C + / O + / S display uncorrelated patterns similar to those in Figs. 3͑c͒ and 3͑d͒, thus confirming the concerted dissociation.…”
Section: Fragment Correlationmentioning
confidence: 69%
“…The Coulomb explosion associated with the Auger process should explain the increase in kinetic energy of the ionic fragments, reflected in the increasing broadening of several fragments. This broadening observed in simple coincidence spectra (PEPICO) and its consequence on the shape of peaks in mass spectra was discussed by Simon et al (1993).…”
Section: Kinetic Energy Of Ionic Fragmentsmentioning
confidence: 93%
“…Following Eland (1989) and Simon et al (1993) the dissociation dynamics of double charge species can be studied by analyzing the coincidence figure (see inset Fig. 14a) of the ions in double coincidence mode in PE2PICO spectra.…”
Section: B) A)mentioning
confidence: 99%
See 1 more Smart Citation
“…The major difference between the two methods is that, in PEPICO the information is extracted from the correlation of the cation with the electron. By contrast, in a PEPIPICO experiment, the information on the various fragmentation pathways is inferred from the correlation maps of the fragment ions, defined by plotting the arrival time of the second fragment at the detector versus the flight time of the first ion [45] [53]. Depending on the progress of the fission, the pattern of the coincidence map will be different, as described in a very comprehensive manner in ref.…”
Section: Electron Ion Ion Coincidence (Pepipico)mentioning
confidence: 99%